Thermodynamics and kinetics for base-pair opening in the P1 duplex of the Tetrahymena group I ribozyme - Lee, Joon-Hwa (Oxford University Press, 2007)
The thermodynamics and kinetics for base-pair opening of the P1 duplex of the Tetrahymena group I ribozyme were studied by NMR hydrogen exchange experiments. The apparent equilibrium constants for base pair opening were measured for most of the imino protons in the P1 duplex using the base catalysts NH(3), [Formula: see text] or TRIS. These equilibrium constants were also measured for several modified P1 duplexes, and the C-2·G23 base pair was the most stable base pair in all the duplexes. The conserved U-1·G22 base pair is required for activity of the ribozyme and the data here show that this wobble base pair destabilizes neighboring base pairs on only one side of the wobble. A 2′-OMe modification on the U-3 residue stabilized its own base pair but had little effect on the neighboring base pairs. Three base pairs, U-1·G22, C-2·G23 and A2·U21 showed unusual equilibrium constants for opening and possible implications of the opening thermodynamics of these base pairs on the undocking rates of the P1 helix with catalytic core are discussed.